The effects of self-encouragement training on distress tolerance among the mothers of hospitalized children - Fahimeh Akbarzadeh; Narges Sadeghi; Maryam Radmehr (Shahrekord University of Medical Sciences, 2022)
Background and aims: The crisis of children's illnesses and their hospitalization is often a main source of stress and anxiety for family members and threatens distress tolerance (DT) among parents, particularly mothers. Self-encouragement training (SET) is one of the strategies with potential positive effects on DT. The present study aimed at evaluating the effects of SET on DT among the mothers of hospitalized children. Methods: This quasi-experimental study was conducted in 2019. Participants were sixty mothers whose children were hospitalized in Ghadir subspecialty pediatric hospital, Shiraz, Iran. They were conveniently selected and randomly allocated to an intervention and a control group. Participants in the intervention group received SET based on the Schoenaker method in ten one-hour sessions in five days, while their counterparts in the control group received no SET. Data were collected using a demographic questionnaire and the Distress Tolerance Scale and were analyzed using the SPSS software (v. 22.0) and the independent-sample and the paired samples t tests. Results: There was no significant difference between the intervention and the control groups respecting the pretest mean score of DT (39.17±8.39 vs. 41.55±10.28; P=0.33), while the posttest mean score of DT in the intervention group was significantly more than the control group (51.23±6.95 vs. 41.23±10.26; P<0.001). Conclusion: SET is effective in significantly improving DT among the mothers of hospitalized children. Nursing managers can use SET to improve DT among these mothers.